The Tale of Two Civil Societies: Comparing disability rights movements in Nicaragua and Uruguay - Meyers, Stephen; Lockwood, Elizabeth (Disability Studies Quarterly, 2014)
The UNCRPD is unique amongst international rights instruments because it empowers civil society organizations to represent the rights-bearers themselves—persons with disabilities. As such, DPOs in the Global South have become a major concern for UN agencies and international NGOs who believe that grassroots disability associations need political advocacy training in order to take up their role as rights advocates. These expectations contain implicit assumptions regarding civil society-state relations and the existence of governmental capacity. The authors, however, hypothesize that not all civil societies will fit the rights advocacy model due to the political culture and public resources available within their respective, local communities. Disability movements in Nicaragua and Uruguay are compared and contrasted. In Nicaragua, a disability rights coalition dismisses many international expectations in favor for continuing to follow traditional civil society expectations to provide services. In Uruguay, a long history of high levels of social spending and disability organizing enabled DPOs to successfully advocate for progressive laws. The deaf community, however, decided to implement their own, separate advocacy strategies to ensure a fairer distribution of public resources. The authors conclude that rather than top-down civil society training, the international movement should allow local organizations set their own priorities.